2000
DOI: 10.1038/sj.onc.1203275
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of response to chemotherapy in transgenic mouse mammary and salivary tumors

Abstract: Several transgenic mouse tumor models were utilized to explore how speci®c genetic alterations aect the tumor cell response to chemotherapeutic agents in vivo. Speci®cally, MMTV-ras transgenic mice were interbred to p53 knock-out mice to create a model for assessing the role of p53 in chemotherapeutic responses. In addition, MMTV-ras tumors were compared to MMTV-myc and MMTV-ras/myc tumors. Mice of each genotype reproducibly develop mammary and/or salivary tumors, but tumor growth dynamics vary considerably be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 39 publications
1
29
1
Order By: Relevance
“…Thus, in our leukemia model downregulation of p21 WAF1 by c-Myc does not switch the p53 activity from cytostatic to proapoptotic, as has been found in colon cancer cells (Seoane et al, 2002). Our results are in agreement with the lack of effect of p21 WAF1 on Myc-induced apoptosis of mammary cells in vivo (Bearss et al, 2002). As BAX is a proapoptotic protein induced by p53, a defective upregulation of BAX in cells expressing c-Myc could explain the apoptosis reduction.…”
Section: How Does C-myc Impair the P53-mediated Apoptosis In K562 Cells?supporting
confidence: 81%
“…Thus, in our leukemia model downregulation of p21 WAF1 by c-Myc does not switch the p53 activity from cytostatic to proapoptotic, as has been found in colon cancer cells (Seoane et al, 2002). Our results are in agreement with the lack of effect of p21 WAF1 on Myc-induced apoptosis of mammary cells in vivo (Bearss et al, 2002). As BAX is a proapoptotic protein induced by p53, a defective upregulation of BAX in cells expressing c-Myc could explain the apoptosis reduction.…”
Section: How Does C-myc Impair the P53-mediated Apoptosis In K562 Cells?supporting
confidence: 81%
“…These and other might also shed some light on their e ects on anti-telomerase therapy for hematologic neoplasias (Bearss et al, 2000). For example, Tauchi et al (unpublished data) have demonstrated that inhibition of telomerase using a dominant negative (DN)-hTERT expression vector in BCR/ABL-transformed cells leads to progressive telomere shortening and apoptosis.…”
Section: Anti-telomerase Therapy For the Hematologic Neplasiamentioning
confidence: 99%
“…The role of these proteins in facilitating tumor formation and development has also been demonstrated in combination with other genetic alterations. Thus, the absence of p21 accelerates the development of some tumors, such us pituitary tumors in Rb-haploinsufficient mice and in INK4c-null mice (Brugarolas et al, 1998;Franklin et al, 2000), breast tumors in Ras transgenic mice (Adnane et al, 2000;Bearss et al, 2002) and intestinal tumors in Apc-haploinsufficient mice (Yang et al, 2001). In contrast, the absence of p21 has no effect on the tumor-prone phenotype of mice deficient for the Werner syndrome gene (Lebel et al, 2001), nor in Myc-induced lymphomas (Martins and Berns, 2002) and mammary tumors (Bearss et al, 2002).…”
Section: Introductionmentioning
confidence: 99%